Impact of CFTR Modulation on Intestinal pH, Motility, and Clinical Outcomes in Patients With Cystic Fibrosis and the G551D Mutation. Issue 3 (March 2017) - Gelfond, Daniel; Heltshe, Sonya; Ma, Changxing; Rowe, Steven M; Frederick, Carla; Uluer, Ahmet; Sicilian, Leonard; Konstan, Michael; Tullis, Elizabeth; Roach, Christine R N; Griffin, Katherine; Joseloff, Elizabeth; et al.
Abstract : OBJECTIVES: : A defect in bicarbonate secretion contributes to the pathophysiology of gastrointestinal complications in patients with cystic fibrosis (CF). We measured gastrointestinal pH, clinical outcomes, and intestinal transit profiles in patients with the G551D mutation before and after treatment with ivacaftor, a CF transmembrane regulator channel (CFTR) potentiator. METHODS: : Observational studies of ivacaftor effectiveness were conducted in the United States and Canada. A subset of subjects ingested a wireless motility capsule ( n =10) that measures in vivo pH, both before therapy with ivacaftor and 1 month after treatment; values obtained were compared for mean pH and area under the pH curve, and regional intestinal motility. We also queried subjects about abdominal pain and recorded body weight before and after treatment. RESULTS: : One month after administering ivacaftor, a significant increase in mean pH was observed after gastric emptying ( P <0.05). Area under the pH curve analyses indicate increased bicarbonate mass ( P <0.05 for select 5 min intervals and all segments >30 min); mean weight gain was 1.1 kg ( P =0.08). No difference in abdominal pain or regional transit times was seen. CONCLUSIONS: : CFTR modulation improves the proximal small intestinal pH profile in patients with the G551D CFTR mutation and we observed clinically relevant, contemporaneous weight gain, although it did not reach statistical significance. These data provide in vivo evidence that CFTR is an important regulator of bicarbonate secretion, which may be a translational link between CFTR function and clinical improvement.